An Overview on Register Language Forms in Animal Feed Buying and Selling Activities in Wonosobo Central Market - Riyanton, M; Kariadi, Mustasyfa Thabib; Setiani, Umi Ana; Anggraheni, Dini; Supriyono, Supriyono (Jurnal Bahasa Inggris, 2020)
This research described the register forms and functions in animal feed buying and selling activities in Wonosobo Central Market and their uses as a learning reference for the Indonesian negotiation text materials. This is a descriptive-qualitative research. The data in this research were utterances containing registers obtained from the animal feed buying and selling activities in Wonosobo Central Market. Based on the research results, there were 28 registers used in animal feed buying and selling activities in Wonosobo Central Market. Those registers were in the form of words, phrases, abbreviations, and acronyms. The registers were 12 root words, 5 words with affix, 3 compound words, 1 repeated word, 1 phrase, 5 abbreviations, and 1 acronym. Each register has a special meaning and it is only known in animal feed buying and selling activities. The obtained data might be used in the negotiation text learning for the X grade students of Senior High School on Basic Competency (Kompetensi Dasar) 3.0 which evaluates the submission, offering, and agreement in spoken and written negotiation texts